Techno-Economic analysis of CAZRI Solar Dryer - PRAKASH, OM; JAIN, DILIP; SRIVASTAV, SOMA; KISHORE, PRABHAT (The Indian Journal of Agricultural Sciences, 2022)
Apricot (Prunus armeniaca L.) is one of the major horticultural produce and an important source of income as well as livelihood in Ladakh, Himachal Pradesh and North-eastern part of India. However, it is also full of nutritional and functional health benefits. Despite all the advantages associated with the fruit, shorter shelf life is major hindrance in attaining its potential economic benefit to the farmers. Apricot drying is most common in these regions t raditionally done by the farmers. Solar dryer developed by ICAR-Central Arid Zone Research Institute (CAZRI) at its regional station, Leh is helping in extending shelf life of apricot and its availability throughout the year. This study was carried out during 2017–19 aimed to estimate the techno-economic benefit on adoption of the dryer by individual farmer or processor. It is found that adopter need to make investment of `1.10 lakh in fixed capital and requires `1.22 lakh annually to process one metric tonnes of the fruit. The annual cost of production was determined as `133,000 with depreciation of `11,000 for project of 1 metric tonne fresh fruit. Estimates indicate that adopter could generate net income of `78,000 annually. Profitability analysis yielded net profit ratio, pay-back period, benefit-cost ratio and break-even point of 37%, 1.23 years, 1.52, and 123.50 kg, respectively.